2011
DOI: 10.1093/treephys/tpr036
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbohydrate reserves in yield production of intensively cultivated oil olive (Olea europaea L.) trees

Abstract: Olive (Olea europaea) has a very high tendency for year-to-year deviation in yield (alternate bearing), which has a negative economic impact on the olive oil industry. Among possible reasons for alternate bearing, depletion of stored carbohydrates (CHO) during the On-year (high yield) has often been mentioned. The objective of the present study was to verify the role of CHO reserves, as a cause or effect, in the alternate bearing of intensively cultivated olives. A monthly survey of soluble sugar and starch co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 45 publications
4
61
1
1
Order By: Relevance
“…Proietti (2000) reported no clear correlation between heavy fruit load and photosynthesis effi ciency, concluding that the depletion of carbohydrate reserves during an "on" year could negatively infl uence new leaves and thus fl ower bud formation. However, Bustan et al (2011) recently showed that carbohydrate surplus or defi ciency cannot be considered the cause of olive alternate bearing, thus, this phenomenon is probably regulated by hormonal factors (Stutte and Martin 1986;Ulger et al, 2004;Dag et al, 2009Dag et al, , 2010. On the whole, carbohydrate resources fl uctuate in response to sharp changes in source-sink relationships in the tree throughout the season playing a role in olive survival strategy (Bustan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proietti (2000) reported no clear correlation between heavy fruit load and photosynthesis effi ciency, concluding that the depletion of carbohydrate reserves during an "on" year could negatively infl uence new leaves and thus fl ower bud formation. However, Bustan et al (2011) recently showed that carbohydrate surplus or defi ciency cannot be considered the cause of olive alternate bearing, thus, this phenomenon is probably regulated by hormonal factors (Stutte and Martin 1986;Ulger et al, 2004;Dag et al, 2009Dag et al, , 2010. On the whole, carbohydrate resources fl uctuate in response to sharp changes in source-sink relationships in the tree throughout the season playing a role in olive survival strategy (Bustan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, Bustan et al (2011) recently showed that carbohydrate surplus or defi ciency cannot be considered the cause of olive alternate bearing, thus, this phenomenon is probably regulated by hormonal factors (Stutte and Martin 1986;Ulger et al, 2004;Dag et al, 2009Dag et al, , 2010. On the whole, carbohydrate resources fl uctuate in response to sharp changes in source-sink relationships in the tree throughout the season playing a role in olive survival strategy (Bustan et al, 2011). Our results suggest that the carbohydrate reserve level may limit mesocarp growth, while pit weight seems to be infl uenced only by the current year's photo-assimilate availability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield estimates from India are often sourced from individual trees rather than being based on the average of a plantation over several seasons [30,34]. For comparison purposes, it is worth noting that the seed yield of commercial orchards of macadamia and almonds tends to range between 5 and 20 kg of nuts in shells per tree per annum, equivalent to about 1 to 6 t per hectare at planting densities of 200 to 320 trees per hectare [13,22,35,41,47]. The lower yield estimates are for non-irrigated groves.…”
Section: Introductionmentioning
confidence: 99%
“…A proeminente redução da respiração foliar parece ter sido peça fundamental nessa regulação, direcionando carboidratos para aumento de reserva e de crescimento, reforçando a partição equilibrada entre esses dois processos. Esses resultados adicionam elementos no entendimento de como ocorreu o efeito de tamponamento observado por quando a mesma espécie foi submetida à elevada concentração de CO 2 acoplada ao alagamento, reforçando a ideia de que a plasticidade presente no sistema de armazenamento da planta (partição entre crescimento e armazenamento equilibrado), bem como a possibilidade de uso destas reservas (disponibilidade) são fatores relevantes a manutenção do crescimento (Bustan et al, 2011;Sala et al, 2012).…”
Section: Considerações Finaisunclassified